The Utilization of Technology in Accommodating Individual Differences and Enhancing Learning Motivation - Nisa barokah; Naimah; Priska Nur (Penerbit Hellow Pustaka, 2025)
Student learning motivation is an important factor in improving the quality of education. In an effort to enhance student learning motivation, technology can be utilized as a tool to create a more engaging and interactive learning environment. This study aims to analyze the effectiveness of technology-based learning methods in increasing student learning motivation in schools. This research employs a literature study method by collecting data from various related articles that have been published.